What Is Lesson Preparation to a Waldorf Teacher, Working Out of Art, Science and Spiritual Philosophy? - Erskine, Josephine Susan (Auckland University of Technology, 2017)
How a unification of art, science and religion can be achieved in education, and whether this can lead to higher levels of knowing This study builds a theoretical basis to support the unification of art, science and religion in education. Understanding and utilisation of this unification is fundamental to Waldorf teaching, and therefore a necessary aspect of lesson preparation by Waldorf teachers. The study compares the historical understanding of these subject domains with more contemporary associations such as wisdom, spirituality, creativity and intelligence. The study reveals how these connect with the values of truth, beauty and goodness, and the activities of thinking, feeling and willing. Building on this, the research demonstrates how resource material for such a teaching process can be organised for lesson preparation, and explores whether such an approach can lead to higher levels of knowing. Stage one of the research used a combination of action research and auto-ethnological methodologies combined with meditative practices to examine how a unification of art, science and religion could be achieved in lesson preparation around a particular theme. Stage two of the research delved into whether and how this unification could lead to a crossing of subject domains, and whether and how it could lead to higher levels of knowing. Stage three of the research involved the compilation of a teacher’s resource book showing examples of how a unification of art, science and religion could be achieved. It forms the creative artifact to this submission. The selection and creation of material for this book formed the main body of the research done in stage one. The analysis of material gathered in stage one, along with further analysis exploring posibilities of higher knowing in stage two, informed the selection of material and layout of the book done in stage three. The outcomes of stages one and two of the research, showed and refined how a combination of art, science and religion could be achieved, and how the crossing of these subject domains was a necessary platform from which higher levels of knowing could develop. It validated the need for a teacher’s resource book that demonstrated a combination of art, science and religion. This book could be of benefit to teachers of all disciplines, but may be particularly helpful to Steiner teachers, where the unification of art, science and religion form the basis of their Waldorf pedagogy. Since recent research shows the success of Waldorf education in developing in its students the responsibilities needed for the twenty first century, a deeper understanding of this approach is valid for all educationalists.
Keywords: Waldorf; Art; Science; Spiritual; Steiner; Teacher training; Teacher preparation; Cross curicular; Learning across domains